2004
DOI: 10.1002/gps.993
|View full text |Cite
|
Sign up to set email alerts
|

Randomized placebo‐controlled trial of donepezil in cognitive impairment in Parkinson's disease

Abstract: Donepezil has a beneficial effect on memory and may improve other cognitive deficits in patients with PD and cognitive impairment. However, variable tolerability in our sample underscores the need for careful monitoring when prescribing donepezil to patients with PD, especially with dosage increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 187 publications
(148 citation statements)
references
References 36 publications
(42 reference statements)
3
143
0
2
Order By: Relevance
“…However, data from clinical trials of anti-dementia agents in the PD setting have been mixed, with some studies reporting a decrease in hallucinations, 28,29 and others reporting no improvement in neuropsychiatric symptoms. [30][31][32] We also observed, from our weighted analysis, that an estimated 16% of patients receiving treatment for PDP have been prescribed risperidone at some point during their course of care. The observation is a potential point of concern in the clinical management of PDP because risperidone is known to exacerbate PD motor symptoms, increase mortality risk in elderly patients with dementia (a common comorbidity among patients with PD), has known interactions with other atypical antipsychotics and is generally not recommended for use in patients with PD.…”
Section: Discussionsupporting
confidence: 52%
“…However, data from clinical trials of anti-dementia agents in the PD setting have been mixed, with some studies reporting a decrease in hallucinations, 28,29 and others reporting no improvement in neuropsychiatric symptoms. [30][31][32] We also observed, from our weighted analysis, that an estimated 16% of patients receiving treatment for PDP have been prescribed risperidone at some point during their course of care. The observation is a potential point of concern in the clinical management of PDP because risperidone is known to exacerbate PD motor symptoms, increase mortality risk in elderly patients with dementia (a common comorbidity among patients with PD), has known interactions with other atypical antipsychotics and is generally not recommended for use in patients with PD.…”
Section: Discussionsupporting
confidence: 52%
“…Hallucinations improved in seven of nine patients. Parkinsonism improved in six individuals, but a slight worsening of tremor was observed in three (Leroi et al, 2004). In another randomized, doubleblind and placebo-controlled study, which involved 16 patients, donepezil improved significantly the subscales of memory.…”
Section: Pd Dementia X Dementia In Normal Pressurementioning
confidence: 90%
“…Though, applications of most of the drugs are still debated. However, the efficacies of the drugs like Donepezil, Atomoxetine, and Citicoline cannot be ruled out owing to their promises [43]. Earlier it was believed that, the occurrence of cognitive impairment in PD is limited to mid-to-late stage of the disease progress but, recent progress of research have showed that, mild cognitive changes is quite common in early stages of PD and hence, opening an avenue of research scope for early diagnosis of the disease.…”
Section: Reviewmentioning
confidence: 99%